Worker displacement in transition economies and in China - Hartmut Lehmann (IZA World of Labor, 2014)
Continuous enterprise restructuring is needed for the transition and emerging market economies to become and remain competitive. However, the beneficial effects of restructuring in the medium run are accompanied by large worker displacement. The costs of displacement can be large and long-lasting for some workers and for the economy. To devise the right policy interventions, governments need to fully understand which workers are displaced and what costs they bear.
Keywords: J64; J65; P50; 330; worker displacement; job loss; transition; emerging economies